#TITLE_ALTERNATIVE# - TAUFAN ADHARSYAH (NIM : 12908004); Dosen Pembimbing : Dr. Eng.Hamzah Latief, MUHAMAD
This study describe about the model of monochromatic wave propagation from deep to shallow waters and nearshore current induced by wave field in surf zone. The wave model uses mild slope equation which is given by Berkhoff (1976). This equation is solved by finite difference, within the numerical technique by a square grid system in a staggered grid scheme. Wave model simulation results are then compared with the results of physical model. This comparison showed a good agree with mean relative error of 23% for cases of waves crashing on breakwater, and 14% for the case of waves crashing on the jetty. Furthermore, comparison between the results of the longshore current model with analytic solutions using the Longuet-Higgins method (1970b) on the synthetic beach give an mean relative error of 17% for the beach slope of 1/25 and 30% for the beach slope of 1/200. The models of wave field and currents are then applied in real case of the Gunaksa Harbour to test the ability of the models. Wave data used were obtained from the calculation using the SMB (Sverdrup-Munk-Bretschneider). Furthermore, the results of the wave field model is used in the wave induced current model. The models results show a phenomenon of superposition in front of the breakwater and attenuation in its behind, and also the nearshore current pattern along the shore and at surrounding the breakwaters due to the wave field.